1993
DOI: 10.1111/j.1476-5381.1993.tb13733.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathways involved in the acute potentiation of NMDA responses by 1S,3R‐ACPD in rat hippocampal slices

Abstract: 1 A grease-gap recording technique has been used to investigate the mechanisms underlying the acute potentiation of N-methyl-D-aspartate (NMDA) responses by aminocyclopentane-1S,3R-dicarboxylic acid (IS,3R-ACPD) in area CAI of rat hippocampal slices.2 1S,3R-ACPD (1OM), but not IR,3S-ACPD (1OEM), potentiated submaximal responses to NMDA (dose-ratio of 0.81 ± 0.02 (mean ± s.e.mean); n = 55), but not to a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), in a readily reversible manner. Potentiation also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
1
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 40 publications
(54 reference statements)
8
82
1
1
Order By: Relevance
“…At low concentrations, NMDA potentiates lS,3R-ACPD-stimulated Ins(1,4,5)P3 accumulation, probably by increasing intracellular Ca2" concentration and facilitation of agonist-stimulated PI-PLC activity. These observations suggest that as well as NMDA-receptor/ion channel activity being affected by metabotropic receptor activation (Bleakman et al, 1992;Courtney & Nicholls, 1992;Chen & Huang, 1992;Kelso et al, 1992;Harvey & Collingridge, 1993), reciprocal modulations can also occur, providing additional evidence for the complexities of ionotropic/ metabotropic 'cross-talk' between glutamate receptors which are considered to underlie phenomena such as synaptic plasticity (Madison et al, 1991;Bashir et al, 1993;Behnisch & Reymann, 1993;Bliss & Collingridge, 1993). In contrast, exposure of neonatal cerebral cortex slices to higher concentrations of NMDA causes a rapidly developing inhibition of agonist-stimulated phosphoinositide responses which are most likely to be due to an acute, Ca2"-dependent neurotoxic action of NMDA in this brain preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low concentrations, NMDA potentiates lS,3R-ACPD-stimulated Ins(1,4,5)P3 accumulation, probably by increasing intracellular Ca2" concentration and facilitation of agonist-stimulated PI-PLC activity. These observations suggest that as well as NMDA-receptor/ion channel activity being affected by metabotropic receptor activation (Bleakman et al, 1992;Courtney & Nicholls, 1992;Chen & Huang, 1992;Kelso et al, 1992;Harvey & Collingridge, 1993), reciprocal modulations can also occur, providing additional evidence for the complexities of ionotropic/ metabotropic 'cross-talk' between glutamate receptors which are considered to underlie phenomena such as synaptic plasticity (Madison et al, 1991;Bashir et al, 1993;Behnisch & Reymann, 1993;Bliss & Collingridge, 1993). In contrast, exposure of neonatal cerebral cortex slices to higher concentrations of NMDA causes a rapidly developing inhibition of agonist-stimulated phosphoinositide responses which are most likely to be due to an acute, Ca2"-dependent neurotoxic action of NMDA in this brain preparation.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to ionotropic/metabotropic interactions, activation of metabotropic glutamate receptors using a selective agonist (e.g. l-aminocyclopentane-1S,3R-dicarboxylic acid (1S,3R-ACPD)) can potentiate NMDA receptor-mediated responses (Bleakman et al, 1992;Harvey & Collingridge, 1993), and co-activation of metabotropic and NMDA receptors has been implicated as a necessary requirement for induction and maintenance of long-term potentiation (Zheng & Gallagher, 1992;Bashir et al, 1993;Behnisch & Reymann, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies have demonstrated enhancement of NMDA responses upon activation of mGluRs (31)(32)(33)(34), but inhibitory effects mediated through group 1 (PLClinked) mGluRs have also been reported (35)(36)(37)(38). The inhibitory pathway varies, being via generation of diacylglycerol and protein kinase C activation (mimicked by 4␤-phorbol 12,13-dibutyrate; Ref.…”
Section: Discussionmentioning
confidence: 99%
“…One prominent effect of mGluR activation in many neuronal populations is an enhancement of agonist-evoked currents through NMDA receptor channels (Aniksztejn et al, 1991;Jones and Headley, 1995;Bleakman et al, 1992;Harvey and Collingridge, 1993;Fitzjohn et al, 1996;Pisani et al, 1997;Awad et al, 2000). In each of these cases, mGluR-induced potentiation of NMDA receptor currents is mediated by a group I mGluR.…”
Section: Introductionmentioning
confidence: 99%